2013
DOI: 10.1039/c3ee40701b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the drivers of regional trends in solar photovoltaic manufacturing

Abstract: The photovoltaic (PV) industry has grown rapidly as a source of energy and economic activity. Since 2008, the average manufacturer-sale price of PV modules has declined by over a factor of two, coinciding with a significant increase in the scale of manufacturing in China. Using a bottom-up model for wafer-based silicon PV, we examine both historical and future factory-location decisions from the perspective of a multinational corporation. Our model calculates the cost of PV manufacturing with process step reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 10 publications
3
93
0
Order By: Relevance
“…35 The coefficient − 0.24 on the dummy for China indicates that production cost of firms from China were 22.4% lower than that of firms from other countries during the period of the study. 36 The computed cost difference is close to the 23% difference found in Goodrich et al (2013b). It is to be noted that the costs of firms from China are lower even after accounting for differences in technological factors like conversion efficiency and polysilicon usage.…”
Section: China Dummysupporting
confidence: 63%
See 1 more Smart Citation
“…35 The coefficient − 0.24 on the dummy for China indicates that production cost of firms from China were 22.4% lower than that of firms from other countries during the period of the study. 36 The computed cost difference is close to the 23% difference found in Goodrich et al (2013b). It is to be noted that the costs of firms from China are lower even after accounting for differences in technological factors like conversion efficiency and polysilicon usage.…”
Section: China Dummysupporting
confidence: 63%
“…In its findings (summarized in USITC (2012)), the commission concluded that Chinese firms had received subsidies from the government. The second study, Goodrich et al (2013b), uses an engineering-type factory model to estimate cost differences between U.S. and China. They conclude that subsidies provided by the provincial governments in China (which include low-cost land, free factory space, and subsidized electricity) as well as supply chain advantages (benefits from having a dense regional network of suppliers to supply the scaled up industry in China) contribute to the cost difference between firms in China and the U.S. 38 See Saga (2010) for a discussion on manufacturing process requirements for solar cells of different efficiencies and the implication for production costs.…”
Section: Efficiencymentioning
confidence: 99%
“…The price of PV-modules, for instance, decreased more than 65% between 2007 and 2011, as a result of scale economies in Chinese production, oversupply, and price-dumping. 28 Growing market demand boosted German solar-PV generation, which increased from 6.6 TWh in 2009 to 38.2 TWh in 2016 (Figure 4). But these developments also had unintended negative consequences.…”
Section: Socio-technical Analysis Of the German Electricity Transitiomentioning
confidence: 99%
“…China is now the largest manufacturer of PV modules, with seven of the world's ten largest PV module suppliers [3]. The main reason to the Chinese dominance is the scale and supply-chain development [4].…”
Section: Introductionmentioning
confidence: 99%